Anti-staphylococcal properties of four plant extracts against sensitive and multi-resistant bacterial strains isolated from cattle and rabbits. (December 2017) - Medina, Mayra Fernanda Echeverría; Alaba, Peter Adeniyi; Estrada-Zuñiga, María Elena; Velázquez-Ordoñez, Valente; Barbabosa-Pliego, Alberto; Salem, Mohmaed Z.M.; Alonso-Fresán, María Uxúa; Camacho-Díaz, Luis Miguel; Salem, Abdelfattah Z.M.
Abstract: The aim of this study is to investigate the biopotency of methanolic extracts of Vitex mollis, Psidium guajava, Dalbergia retusa, and Crescential alata leaves against various staphylococcal strains isolated from cattle and rabbits. Methicillin-resistant S. aureus strains were isolated from cattle, while other strains were isolated from rabbits using standard methodology. The total phytochemical phenolic and saponins contents were obtained being the main groups of the antinutritional factors. The antimicrobial activity of the extracts against the standard culture of S. aureus (control) and S. aureus isolated from cattle and rabbits were investigated comparatively relative to that of oxacillin. It was found that both the control S. aureus and the isolated S. aureus are susceptible to all the four plant extracts, and sensitive to oxacillin. Of all the S. aureus including the control, MRSA2 is the most susceptible to all the extracts at 1000 μg/mL, except that of V. mollis where it is the least susceptible. Among all the plant extracts, P. guajava is the most active against MRSA2 and SOSA2. Therefore, the isolates from cattle (MRSA1 and MRSA2) are more susceptible to all the plant extracts than the isolates from rabbits. Among all the rabbit isolates, CoNS3 is the least susceptible to the extracts. Since all the plant extracts exhibit remarkable inhibitory activities against all the S. aureus strains, they are promising towards the production of therapeutic drugs. Graphical abstract: Highlights: Sensitive and multi-resistant bacteria cause for a serious concern in pharmacology. Plant extracts are good source of phytochemicals with anti-staphylococcal property. Extract of V. mollis, P. guajaya, D. retusa, and C. alata are good antibiotics. V. mollis is the best against most of the sensitive and multi-resistant bacterial. Cattle-based bacterial are more susceptible to the extracts than rabbit-based.